Analisis Kebutuhan Sumur Resapan Sebagai Salah Satu Upaya Dalam Mereduksi Banjir Genangan - Meliyana Meliyana; Ichsan Syahputra; Helwiyah Zain; Antoniadi Zal (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
Impermeable land in a region can not absorb rain water, so that rain water becomes run off and cause flood inundation. Absorption wells function to accommodate and absorb rain water into the soil. The purpose of this study to know the value of soil permeability, determine the dimensions and number of absorption wells in reducing flood. The study was conducted at Elementary School 1 Pulo Ie Kabupaten Nagan Raya with area of 1500 m2 and the number of buildings as many as 4 units. The absorption well planning refers to regulation of the Minister of Public Works 11/PRT/M/2014. The data used in the planning form average daily rainfall, flood volume, soil permeability value, runoff coefficient value, depth of ground water level and wide field of cistern. The result of analysis obtained maximum daily rainfall average maximum (R) equal to 36,25 mm/day, volumes of flood (Vab) 11,552 m3, cistern area 497 m2, runoff coefficient value of 0.75 and soil permeability value (K) 0.009725 cm/sec or 8.40 m/day. Rectangular Absorption wells with depth of well (H) 1.60 meters and base well (L) width 1.20 meters. The number of absorption wells required 5 units. Thus, the flood of inundation at the Elementary School 1 Pulo Ie can be accommodated by the absorption wells, so that the flood of inundation can be overcome.